The Role of Probiotics, Prebiotics and Synbiotics in Combating Multidrug - Resistant Organisms - Newman, Andrew (Clin Ther, 2020)
The prevalence of multidrug-resistant organisms is increasing worldwide, posing a unique challenge to global health care systems. Novel approaches are needed to combat the spread of infection with these organisms. The enteric microbiome, and in particular the resistome, offers a unique target in both the prevention of infection with these organisms and the acquisition and spread within the community. We highlight a novel approach to combat multidrug-resistant organisms: the use of prebiotics, probiotics, and synbiotics to manipulate the microbiome and resistome. This review summarizes the published literature and clinical trials related to these products to date, with a focus on efficacious trials. It highlights the probable mechanism of action for each product, as well as its safety profile in selective populations. Ultimately, although further research is needed before a definitive statement can be made on the efficacy of any of these 3 interventions, the literature to date offers new hope and a new tool in the arsenal in the fight against bacterial drug resistance.